2018
DOI: 10.5606/tftrd.2018.2366
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the Q angle and the isokinetic knee strength and muscle activity

Abstract: Objectives: The aim of this study was to investigate the correlation between the Q angle and the isokinetic knee strength and muscle activity. Patients and methods: Between March 2016 and April 2016, a total of 50 healthy and right-leg dominant men (mean age 22.3±2.3 years; range, 18 to 27 years) with a Q angle between 5° and 20° and active in sports were included. An isokinetic strength test of the knee joint extensor and flexor muscles at angular velocities of 60, 120, 180, 240, and 300°•s-1 was tested who h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 30 publications
3
17
0
Order By: Relevance
“…Most researchers found that engaging in a regular sports practice with high lower limb activities would cause the Q-angle to be lower than normal. 31 This was consistent with our results, as group A, who played sports, had lower values than group B. This could be explained by the means of quadriceps muscle strength, in which the higher the muscle strength, the lower the Q-angle.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Most researchers found that engaging in a regular sports practice with high lower limb activities would cause the Q-angle to be lower than normal. 31 This was consistent with our results, as group A, who played sports, had lower values than group B. This could be explained by the means of quadriceps muscle strength, in which the higher the muscle strength, the lower the Q-angle.…”
Section: Discussionsupporting
confidence: 92%
“…This could be explained by the means of quadriceps muscle strength, in which the higher the muscle strength, the lower the Q-angle. 31 …”
Section: Discussionmentioning
confidence: 99%
“…Comparing torque, work and power outputs, Q angle was found to be negatively related to torque and power (Binder, Brown-Cross, Shamus, & Davies, 2001;Hahn & Foldspang, 2007). Our previous study also supports these results (Saç & Taşmektepligil, 2018).…”
Section: Discussionsupporting
confidence: 83%
“…The Q-angle in ACL tear indicates the inferior extremity alignment and indicates that the valgus shape of knee joint in the case group had a smaller mean value compared to the control group. 10,17 It is inconsistent with study by Bayer et a and Sac et al which found that larger Q-angle can increased dynamic valgus and high abduction loads of the knee. 10,17 The case group had a lower MTPS score with a mean value of 9.24±2.73 than the control group, with a mean value of 7.7024±3.53.…”
Section: Discussionmentioning
confidence: 81%
“…However, various measurement techniques and methods of these anatomical factors are still debatable. 1,2,[9][10][11]13,[15][16][17]18 This study aims to provide an overview of anatomical risk factor characteristics in knee joint MRI study.…”
Section: Introductionmentioning
confidence: 99%